Pengembangan Produk Pengetahuan Sebagai Inovasi Layanan Perpustakaan Di Era Industri 4.0 - Mohamad Djaenudin; Tupan Tupan (Ikatan Pustakawan Indonesia, 2020)
A study of knowledge product development was conducted as a library service innovation in the industrial era 4.0. The research aims to find out (1) the types of knowledge products that can be made as library service innovations; and (2) the process of making knowledge products consisting of stages and steps for making them. The study was conducted using descriptive methods with a literature study approach. Research collection is done through observation, and literature study (literature). Observation is done by recording the knowledge products that have been made by PDII LIPI. Literature studies are carried out by examining the ratios related to making knowledge products. The results of the literature review are then analyzed and interpreted in the form of results and discussion. The results showed that the types of knowledge products that could be made as library service innovations in the industrial era 4.0 were the focus of Indonesian information, research on information technology, information on intellectual property rights, literature review, new information, database of fields, executive summary, policy breaf, policy paper, graphic animated films, industrial trees, information technology packages and business guides. The stages of the process of making knowledge products are selecting and defining the topic of knowledge products; determine the source of information; determine the location of information and how to access information; use information by evaluating and citing information; synthesizing namely packaging information into knowledge products; evaluate the product of knowledge made, and evaluate the manufacturing process